Morocco : 2012 Article IV Consultation and First Review Under the Two-Year Precautionary and Liquidity Line-Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2013)
Morocco's sound economic performance has been challenged by domestic and external shocks. The Precautionary and Liquidity Line (PLL) program is on track, and its design remains adequate. The fiscal consolidation and efforts to rebuild buffers and address medium-term challenges taken up by the government has been commended. Reforms of both the subsidy system and the pension system are required. There is a need to strengthen competitiveness and better equip the economy to respond to external shocks. Efforts are under way to continue strengthening regulation and supervision while fostering the development of the financial sector.